Encyclopedia of cancer - Schwab, M. 1945- (Springer, 2017)
This work comprehensively describes etiological factors in the development, Progression and metastasis of human cancers, both for hematological malignancies and for solid Tumors.
Keywords: Cancer -- Encyclopedias.; elektronické knihy; electronic books